Ancient Roots of Modern Medicines; their Prospects and Promises - Shrivastava, Sandeep S.; Kharabe, Pankaj M. (Pharmacognosy Reviews)
Drug development from natural products precedes human history by thousands of years. Mankind has learned to take the advantages of such discovered principles by nature which they now used to treat human diseases. Since, owing to the close evolutionary history with plants and animals species, many metabolites that they produce, mimics the human biological activities such as the neurotransmitters, enzymes and hormones. Therefore, many metabolites that plants and animals produce are now used by human being to treat the diseases like diabetes, cancer, microbial infections and Alzheimer’s disease. The advent of combinatorial chemistry, organic chemistry and high throughput screening (HTS) has developed many lead molecules to treat human diseases. Unfortunately, these renewed techniques did not bring any expected returns in terms of new drug discoveries and therefore many researchers have shifted their research efforts back to the natural products to discover and develop the multidimensional and multibroadspectrum medicines using genomic engineering, combinatorial mucobiosynthesis and modern analytical techniques. In the present review, we have discussed comprehensively the journey of modern medicines with their prospects and promises.
Keywords: Combinatorial chemistry; High throughput screening (HTS); Genomic engineering; Genomic mining; Combinatorial mucobiosynthesis.